Natural biocide cocktails: Combinatorial antibiotic effects of prodigiosin and biosurfactants. - Jennifer Hage-Hülsmann; Alexander Grünberger; Stephan Thies; Beatrix Santiago-Schübel; Andreas Sebastian Klein; Jörg Pietruszka; Dennis Binder; Fabienne Hilgers; Andreas Domröse; Thomas Drepper; Dietrich Kohlheyer; Karl-Erich Jaeger; et al. (PLoS ONE)
Bacterial secondary metabolites are naturally produced to prevail amongst competitors in a shared habitat and thus represent a valuable source for antibiotic discovery. The transformation of newly discovered antibiotic compounds into effective drugs often requires additional surfactant components for drug formulation. Nature may also provide blueprints in this respect: A cocktail of two compounds consisting of the antibacterial red pigment prodigiosin and the biosurfactant serrawettin W1 is naturally produced by the bacterium Serratia marcescens, which occurs in highly competitive habitats including soil. We show here a combinatorial antibacterial effect of these compounds, but also of prodigiosin mixed with other (bio)surfactants, against the soil-dwelling bacterium Corynebacterium glutamicum taken as a model target bacterium. Prodigiosin exerted a combinatorial inhibitory effect with all tested surfactants in a disk diffusion assay which was especially pronounced in combination with N-myristoyltyrosine. Minimal inhibitory and bactericidal concentrations (MIC and MBC) of the individual compounds were 2.56 μg/mL prodigiosin and 32 μg/mL N-myristoyltyrosine, and the MIC of prodigiosin was decreased by 3 orders of magnitude to 0.005 μg/mL in the presence of 16 μg/mL N-myristoyltyrosine, indicative of synergistic interaction. Investigation of bacterial survival revealed similar combinatorial effects; moreover, antagonistic effects were observed at higher compound concentrations. Finally, the investigation of microcolony formation under combined application of concentrations just below the MBC revealed heterogeneity of responses with cell death or delayed growth. In summary, this study describes the combinatorial antibacterial effects of microbial biomolecules, which may have ecological relevance by inhibiting cohabiting species, but shall furthermore inspire drug development in the combat of infectious disease.